Effects of overweight and obesity on motor and mental development in infants and toddlers. Issue 5 (21st October 2015) - Cataldo, R.; Huang, J.; Calixte, R.; Wong, A. T.; Bianchi‐Hayes, J.; Pati, S.
Summary: Background: A consequence of childhood obesity may be poor developmental outcomes. Objectives: This study aimed to examine the relationship between weight and developmental delays in young children. Methods: We conducted a secondary analysis of the Early Childhood Longitudinal Study Birth Cohort data. Logistic regression models quantified the association between different weight statuses (normal weight <85th, overweight ≥90th, obese ≥95th percentile for weight) and delays in motor and mental development. Results: Children classified as overweight in both waves had higher percentages of delays in wave 2 (motor [7.5 vs. 6.2–6.4%], mental [8.6 vs. 5.9–6.7%]), as well as wave 1 and/or wave 2 (motor [14.8 vs. 10.9–13.0%], mental [11.9 vs. 9.0–10.1%]), compared with other children. This association was also found in children who were obese at both time points in wave 2 (motor delay [8.9 vs. 4.9–7.3%], mental delay [10.3 vs. 6.0–7.2%]), as well as wave 1 and/or wave 2 (motor delay [14.5 vs. 10.9–12.9%], mental delay [14.1 vs. 9.4–10.1%]). In the adjusted models, children classified as always obese were more likely to have a mental delay in wave 2 (adjusted odds ratio [aOR] 1.89, 95% confidence interval [CI]: 1.21–2.95) as well as wave 1 and/or wave 2 (aOR 1.56, 95% CI: 1.08–2.26). These children were also more likely to have motor delay (aOR 1.47, 95% CI: 1.02–2.13) in wave 1 and/or wave 2. Conclusion: Overweight children are more likely than their normal‐weight peers to have motor and mental developmental delays. Preventing obesity during infancy may facilitate reducing developmental delays in young children.